2018
DOI: 10.1002/cphc.201701350
|View full text |Cite
|
Sign up to set email alerts
|

On the Synthesis of Chocolate Flavonoids (Propanols, Butanals) in the Interstellar Medium

Abstract: Complex organic molecules are ubiquitous in star- and planet-forming regions as well as on comets such as on 67P/Churyumov-Gerasimenko, but their origins have remained largely unexplained until now. Here, we report the first laboratory detection of distinct C H O (propanol, methyl ethyl ether) and C H O (n-butanal, i-butanal) isomers formed within interstellar analog ices through interaction with ionizing radiation. This study reveals that complex organics with propyl (C H ) and butyl (C H ) groups can be synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…[69] Most important, since the fundamentals of functional groups such as of carbonyls in COMs potentially synthesized during the radiation processing of acetaldehyde often fall in the same range, infrared spectroscopy rarely allows an identification of individual COMs. [63,70] Therefore, an alternative analytical technique is critical to probe discrete organics in the irradiated ices. Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…[69] Most important, since the fundamentals of functional groups such as of carbonyls in COMs potentially synthesized during the radiation processing of acetaldehyde often fall in the same range, infrared spectroscopy rarely allows an identification of individual COMs. [63,70] Therefore, an alternative analytical technique is critical to probe discrete organics in the irradiated ices. Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…Further increasing the interest of n-and i-butanal (also known as n-and i-butyraldehyde and hereafter n-PrCHO and i-PrCHO, respectively) as astronomical candidates, Abplanalp et al (2018) revealed that both isomers -together with distinct C 3 H 8 O species, such as propanol and methyl ethyl ether (the latter was already detected in the ISM toward Orion KL by Tercero et al 2018and toward IRAS 16293-2422A by Manigand et al 2020) -could be generated by exposing interstellar analog ices to ionizing radiation. Therefore, they should be detectable in the gas phase after desorption from the icy grains in regions of star formation (Abplanalp & Kaiser 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Hudson et al (2017) were able to form propanal by proton irradiation of a CO 2 :C 3 H 6 ice mixture at 10 K. H 2 O: 13 CH 3 OH:NH 3 78 K ice exposed to UV photons and heated to room temperature also yielded propanal (de Marcellus et al 2015). Propanol was reported to be formed by electron irradiation of a 13 CO: 13 CD 4 ice mixture at 5 K in experiments that did not allow to discriminate between 1and 2-propanol (Abplanalp et al 2018a).…”
Section: Introductionmentioning
confidence: 99%